2019
DOI: 10.1590/0001-3765201920180047
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of immatures of Dasyhelea flavifrons Guérin-Méneville (Culicomorpha: Ceratopogonidae) and new contribution to the knowledge of its larval habitats

Abstract: The fourth instar larva and pupa of Dasyhelea flavifrons Guérin-Méneville are redescribed, illustrated, and photomicrographed using binocular, phase-contrast, and scanning electron microscopy. Comparisons with the American species of the grisea group were made. The immatures were collected by using a siphon bottle in tree-holes and from water collected in dead snail shells in Salta Province, Argentina, transported to the laboratory and there bred to the emergence of the adults. Details on larval habitats are g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The fourth instar larva of D. silvatica is very similar to its congeners D. azteca Huerta & Grogan by virtue of the antenna being short, the lateral arms of the epipharynx stout and the anterior portion of palatum with four pairs of campaniformia sensilla, but it can be distinguished from the former by the posterior portion of palatum bearing two pairs of coeloconica sensilla, the MD with three teeth, and the MP with only three small papillae. In addition, the fourth instar larva of D. silvatica is also similar to that of D. flavifrons (Guérin-Méneville), recently described by Díaz et al (2019) with the brown head capsule, the posterior portion of palatum with four pairs of campaniformia sensilla and three pairs of coeloconica sensilla, the posterior comb of the hypopharynx has a fringe; however, D. flavifrons differs by the galeolacinia with 5–6 papillae and the MP with only three or four papillae.…”
Section: Discussionsupporting
confidence: 58%
“…The fourth instar larva of D. silvatica is very similar to its congeners D. azteca Huerta & Grogan by virtue of the antenna being short, the lateral arms of the epipharynx stout and the anterior portion of palatum with four pairs of campaniformia sensilla, but it can be distinguished from the former by the posterior portion of palatum bearing two pairs of coeloconica sensilla, the MD with three teeth, and the MP with only three small papillae. In addition, the fourth instar larva of D. silvatica is also similar to that of D. flavifrons (Guérin-Méneville), recently described by Díaz et al (2019) with the brown head capsule, the posterior portion of palatum with four pairs of campaniformia sensilla and three pairs of coeloconica sensilla, the posterior comb of the hypopharynx has a fringe; however, D. flavifrons differs by the galeolacinia with 5–6 papillae and the MP with only three or four papillae.…”
Section: Discussionsupporting
confidence: 58%
“…The NMDS, which considers not only presence but also the abundance per site of each family, showed a clear difference in the composition of the assemblages from each season, which were statistically significant in PERMANOVA. Eight families (Cecidomyiidae, Chloropidae, Chironomidae, Ceratopogonidae, Scatopsidae, Sciaridae, as phytotelmata (Borkent & Spinelli, 2007;Díaz et al, 2019). Murray (1991) found that some breeding continued throughout the winter and Walker (1977) determined that many species of this group would persist in stable populations throughout the year even when rain was scarce.…”
Section: Table III Simper Analysis Of Family Contributions To Dissimilarities Between Summer and Winter Assemblages (Abundance Data Transmentioning
confidence: 99%